Von Büchsen und Burgern. Zum deutschsprachigen Antiamerikanismus innerhalb und außerhalb der schönen Literatur - Dahlmanns, Karsten (Acta Neophilologica, 2023)
In the German-speaking world, anti-Americanism takes many forms. There is an astonishingly persistent distrust of certain products from the USA, e.g. mincemeat, both in its canned or frozen variety, and wine. Canned beer – an American innovation – is also often frowned upon. This essay explores German and Austrian anti-Americanism concerning canned meat, burgers and beverages in literary fiction such as Die andere Seite by Alfred Kubin, non-literary texts and other sources, including the satirical magazine Simplicissismus, Ganz unten by Günter Wallraff, Unter Linken, a film by Jan Fleischhauer, a song by Hans Söllner, and the diaries of Edith Landmann, a close friend, and disciple, of Stefan George.